2007
DOI: 10.1063/1.2768192
|View full text |Cite
|
Sign up to set email alerts
|

Laser induced short plane acoustic wave focusing in water

Abstract: Articles you may be interested inGeneration of inhomogeneous plane shear acoustic modes by laser-induced thermoelastic gratings at the interface of transparent and opaque solids Laser induced plane acoustic wave generation, propagation, and interaction with rigid structures in water J. Appl. Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…Moreover, thin films are optimal for generating sound waves perpendicular to the target surface. Propagation of sound waves in the direction perpendicular to the surface of chromium film from laser irradiation was extensively studied by Ko et al 13 Sound waves with different parameters (amplitude, frequency, etc.) can be formed by different generation mechanisms; however, the strongest ultrasound signal is generated from a surface vibration in the direction perpendicular to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, thin films are optimal for generating sound waves perpendicular to the target surface. Propagation of sound waves in the direction perpendicular to the surface of chromium film from laser irradiation was extensively studied by Ko et al 13 Sound waves with different parameters (amplitude, frequency, etc.) can be formed by different generation mechanisms; however, the strongest ultrasound signal is generated from a surface vibration in the direction perpendicular to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…A calculation has shown that the penetration depth for a 4 MHz acoustic wave traveling in glycerin is about 8 mm. 24,25 The high attenuation may also cause a decrease in the contribution of the waves generated from the outer electrodes to the interference, making the axial pressure distributions of the three FZPs become similar ͑Fig. 5͒.…”
Section: ͑4͒mentioning
confidence: 99%
“…The momentum of the plasma plume becomes the impulse or the excitation force for the irradiated material. LA has various applications, including plasma growth, 23 LA shockwave in air, 24 LA in water, 25 cavitation bubble, 26 laser propulsion, 27,28 laser micromachining, 29 laser deposition, 30 laser peening, 31 and vibration tests and acoustic tests using LA or laser-induced breakdown (LIB). [32][33][34][35][36][37][38][39][40][41] Although multiple stress waves in silica glass generated by femtosecond LA 20 have been visualized using the shadowgraph technique, using LA as an excitation force for gels has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%